Hardness and toughness evaluation of developed Al metal matrix composite using stir casting method. (2020) - Chandra, Divya; Chauhan, Nathi Ram; Rajesha, S.
Abstract: Composite materials have many unique properties which mostly conventional materials usually do not comprise. One of these properties is the better volume to weight ratio which is very useful for designing of components of aircrafts, automobiles, domestic appliances and electronic devices. However some challenges occur in development of homogenous metal matrix composites because of different phases of matrix material and reinforcement materials. In this study, three different aluminium based metal matrix composites have been developed by varying the percentage of matrix (Al6063) and reinforcement (flyash and Al2 O3 ) materials by using stir casting method and after that the hardness and toughness have been determined. Stir casting method has been used because of its low cost setup and portability. Result shows that the contribution of Al2 O3 particles plays an important role in increasing the hardness of composite material.